Computer-aided simulation of unmanned aerial vehicle composite structure dynamics - Kierzkowski, Artur; Kisiel, Tomasz; Milewski, Maciej; Török, Ádám; Stosiak, Michał; Wróbel, Jakub (Transport, 2024)
The dynamic response of an aerial vehicle structure is a key parameter that must be determined before further aeroelastic phenomena can be analysed in the aerospace sector. Natural frequencies, mode shapes, and damping can be measured or predicted through experimental, operational, or computational studies. To reduce the costs and complexity of experimental investigations, there is a demand for numerical models that accurately represent the structure′s dynamic behaviour. This article focuses on modelling composite structures, which are increasingly utilised in the aerospace industry and whose dynamic properties are heavily influenced by fibre directionality. ANSYS software and the ACP module were employed to develop a numerical model of a wet Epoxy Carbon UD (230 GPa) composite commonly used in Unmanned Aerial Vehicle (UAV) components. Ten layers of 0.1 mm thick carbon fibre were incorporated into the model to create a 1 mm thick composite plate, with fibres oriented at 0°, 30°, 45°, and 90° relative to the horizontal direction of the plate. The simulations demonstrated that careful consideration and modelling of the material significantly impact the values of natural frequencies and, more importantly, the mode shapes. First published online 28 January 2025